Republic of Tajikistan : 2019 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Reported economic activity has been strong in 2018-19 and inflation has picked up. The monetary framework is being strengthened. The external position has deteriorated. The fiscal deficit has widened as revenues have declined. Reforms to place the loss-making energy sector on a sound financial footing are underway. The authorities' development strategy relies on large infrastructure projects- Roghun dam and other large SOE-implemented projects - that need sizable external financing. The financial sector is recovering from the 2015-16 crisis, with a decline in nonperforming loans and improved profitability. The authorities are making efforts to strengthen bank supervision and regulation. However, two formerly-systemic banks remain insolvent and further reforms are needed to restore public confidence in banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Tajikistan, Republic of